The Role Of The Principal In Forming Students' Social Care Characters At Smpn 3 Bandar Dua Pidie Jaya - Meutia S; Nazaruddin Abdullah; Nazaruddin Ismail (Journal of Pedagogi, 2025)
This study aims to explain the role of the principal in forming a socially caring character through a descriptive qualitative approach. Data were obtained from interviews, observations, and documentation of the principal, teachers, and students. The findings show that the principal plays an active role with four main steps: (1) formulating structured policies for social programs, (2) encouraging the implementation of sustainable programs such as community service and fundraising, (3) being a role model in social activities, and (4) monitoring and providing full support so that the values of social care are internalized. The impact is seen from the increase in empathy and mutual respect behavior among students. The main supporting factors are the principal's commitment and teacher involvement, while inhibiting factors include lack of parental support and limited student time. This study recommends increasing parental involvement and strengthening character education programs to form a more optimal socially caring character